The Effect of Mixed Method Training Circuit Training Ladder Drill on Agility and Speed Run - Utomo, Ardyansyah Arief Budi; Nurhasan, Nurhasan; Wiriawan, Oce; Muhammad, Heryanto Nur (International Journal of Emerging Research and Review, 2024)
Objectives: The ladder drill training method to increase agility and speed (speed run) has not been combined in much research. This research tries to combine them in order to improve the quality of professional futsal athletes. Method:  The research approach used in this research is a quantitative approach. This type of research uses a quasi experiment or quasi experiment. This research design uses a matching only design research design . This research variable consists of 1 independent variable (circuit training ladder drill) and 2 dependent variables ( agility and speed ). The population is 100 professional futsal athletes in Madiun City, and the sample is 30 people. This research is only specifically for male samples aged between 18-20 years. The sample was divided into 2 groups, namely the ladder drill circuit training experimental group and the control group. The research instrument used a hexagonal obstacle test and a 30 meter acceleration test. Data collection techniques were carried out first by carrying out normality tests and homogeneity tests. Data analysis techniques were carried out using the formula mean , standard deviation , variance , percentage increase, paired sample t test , one way anova test , and post hoc comparison. Results: There was a difference in agility before and after giving the mixed method training circuit training ladder drill. The difference in agility is shown from the results of parametric statistical analysis using a paired sample t test with the significance value in the sig column showing sig 0.000 < α 0.05. Novelty: The novelty in this research is combining the ladder drill training method to increase agility and speed run aimed at professional futsal athletes.